Transesterification of Refined, Bleached and Deodorised Palm Olein and Palm Oil in Organic Solvents by Immobilised Rhizomucor Miehei Lipase - Ahamad Zakeri, Hazlina (2002)
The effects of medium's hydrophobicity and reaction temperatures on Rhizomucor miehei lipase-catalysed transesterification of refined, bleached and deodorised (RBO) palm olein and RBD palm oil were studied. Solvents with log P values ranging from -1.3-4.52 were chosen. The extent of trans esterification was studied based on whether there was an increase in the triglyceride composition or if there were new triglycerides formed. Analyses on the triglyceride composition, melting properties and slip melting point of transesterified OIls were eamed out. Solvents with log P values between 2 and 4 (2 ≤ log P < 4) and more than 4 (log P≥ 4) were found to give the highest degree of transesterification in palm olein and palm oil. Solvents such as hexane (log P 3.5) and isooctane (log P 4.52) were found to be particular1y useful in both transesterification of palm olein and palm oil. No transesterification took place in solvents with log P less than 2 (log P < 2). The effect of reaction temperatures was studied using isooctane and hexane. Transesterification rates were found to increase as the reaction temperatures ina-eased indicating that the lipase was stable at high temperatures in organic solvents. The highest degree of transesterification was found at 60˚C. A lower degree of transesterification was found in palm oil transesterified at 300C. Two new triglycerides were synthesised at the end of the transesterification of palm olein, namely, tripalmitin (PPP) and distearoyi-oleoyl glycerol (SOS). No new triglycerides were funned in transesterified palm oil. Changes in the composition of several original triglycerides were also obtained in transesterifled palm olein and palm oil. Melting properties of transesterified oil depended in general, on the chemical composition of the oils. Due to the complexity of the triglycerides, the heating curves were not easily interpretable. Formation of tripalmitin was found to be the cause of a new peak formed in the heating curve of transesterified palm olein. The slip melting point of palm olein and palm oil increased after transesterification. Exception was noted for transesterified palm oil at different reaction temperatures in isooctane and hexane incubated for longer incubation period where the slip melting point decreased. The white partides formed after transesterification of palm olein at 40˚C shaked for 6 hours at 200 revmin-1 were found to contain high melting glycerides, which were dominated by tripalmitin. The high melting glycerides were also high in palmitic acids with trace amount of oleic, stearic and linoleic acids. The heating curve of high melting glycerides consisted of a sharp and more prominent high-T peak and a small low-T peak. Due to the triglyceride composition of high melting glycerides, its Slip melting point was found to be at 59°C.